"The industrial union is the embryo of the socialist commonwealth": The International Socialist League and revolutionary syndicalism in South Africa, 1915-1919 - Van der Walt, Lucien (My University, 1998)
The outbreak of the First World War in Europe in August 1914 was a turning point in the history of the international socialist and radical labour movement. The war precipitated the collapse of the International Socialist Bureau (the "Second International") of socialist and labour parties, with almost all sections supporting the war efforts of their national governments. The only Second International groupings which proved exceptions to this general pattern -a violation of every basic tent of the international socialism, as well as the formal anti-war commitments of the Second International - were the Russian Bolsheviks, the Serbian socialists, and anti-war minorities in a few of the belligerent parties.
African Studies Seminar series. Paper presented 12 October 1998
Keywords: International Socialist League (S.A.). History; Syndicalism. South Africa. History; Socialism. South Africa. History; Labor movement. South Africa. History